Pengujian Intensitas Cahaya pada Ruang Laboratorium Komputer Fakultas Sains Dan Teknik (FST) Undana Menggunakan Calculux V.5.0 - Nursalim, Nursalim; Kurniati, Sri; Kabelen, Aloysius L (Jurnal Media Elektro, 2013)
This study aims to determine the large intensity lighting (Eaverage) based benchmark Indonesian National Standard (SNI) at the Computer Laboratory of the Faculty of Science and Engineering (FST) is 500 Lux by of direct measurement, data analysis and simulation using software Calculux. Based on the results of the measurement, calculation and analysis of large value obtained Eaverage of 304.398 lux, so it can be seen that the laboratory has not reached the recommended ISO standards for laboratories. It is necessary for the simulation to achieve compliance in accordance with the ISO using Calculux v5.0. After performing simulations to obtain the fulfillment of the ISO standard, showed that the amount of light on a computer lab is 8 units (304 398 lux) should beÂ  increased to 10 pieces with the same kind of light, so that it can reach the standards set, which is equal to 500 lux.